2018
DOI: 10.37236/6303
|View full text |Cite
|
Sign up to set email alerts
|

Extension from Precoloured Sets of Edges

Abstract: We consider precolouring extension problems for proper edge-colourings of graphs and multigraphs, in an attempt to prove stronger versions of Vizing's and Shannon's bounds on the chromatic index of (multi)graphs in terms of their maximum degree ∆. We are especially interested in the following question: when is it possible to extend a precoloured matching to a colouring of all edges of a (multi)graph? This question turns out to be related to the notorious List Colouring Conjecture and other classic notions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 31 publications
(110 reference statements)
0
32
0
Order By: Relevance
“…The case d = t = 1 of Theorem 5 was previously established by Edwards, Girão, van den Heuvel, Kang, Sereni and the third author [5], with the slightly stronger assumption of ∆ ≥ 19. (Note that the restriction of our proof for Theorem 2 to this case provides a somewhat new proof; both arguments use global discharging, but we discharge in a different way).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The case d = t = 1 of Theorem 5 was previously established by Edwards, Girão, van den Heuvel, Kang, Sereni and the third author [5], with the slightly stronger assumption of ∆ ≥ 19. (Note that the restriction of our proof for Theorem 2 to this case provides a somewhat new proof; both arguments use global discharging, but we discharge in a different way).…”
Section: Introductionmentioning
confidence: 83%
“…As Edwards et al [5] observed, extending an edge-colouring is closely related to list-edge-colouring. An edge list assignment on a graph G is a function L that assigns to each edge e ∈ E(G) a list of colours L(e).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although matching extendability and subgraph containment problems have been studied extensively for hypercubes (see, eg, [8,11,18,19] and references therein), the edge precoloring extension problem for hypercubes seems to be a hitherto quite unexplored line of research. As in the setting of completing partial Latin squares (and unlike the papers [5,10]) we consider only proper edge colorings of hypercubes Q d using exactly Q Δ( ) d colors. We prove that every edge precoloring of the d-dimensional hypercube Q d with at most d − 1 precolored edges is extendable to a d-edge coloring of Q d , thereby establishing an analogue of the positive resolution of Evans' conjecture.…”
Section: Introductionmentioning
confidence: 99%